1973
DOI: 10.1104/pp.51.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Auxin Inhibition of Ripening in Bartlett Pears

Abstract: The effect of indoleacetic acid and 2, 4-dichlorophenoxyacetic acid on the ripening of intact mature-green pears (Pyrus communis var. Bartlett) was investigated using a vacuum infiltration technique.The effects of indoleacetic acid and 2, 4-dichlorophenoxyacetic acid at concentrations of 0.01, 0.1, and 1.0 mM each were studied on softening, degreening, and on ethylene and C02 evolution. Softening and degreening were inhibited increasingly in response to increased concentrations of indoleacetic acid.This inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1
2

Year Published

1975
1975
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 14 publications
2
67
1
2
Order By: Relevance
“…MdGH3.18 was highly expressed at the early stages but decreasing trend as fruit reached physiological maturity, which is opposite to the expression profile of MdGH3.18; and a much higher expression level was observed in CP than in GD. Auxin has long been considered a natural inhibitor for fruit ripening as the concentration of auxin is low during pear ripening [57]. It was also observed that as apple ripening began, auxin concentration decreased and ethylene concentration increased [58].…”
Section: The Expression Of Auxin-related Genes and Ethylene Biosynthementioning
confidence: 80%
“…MdGH3.18 was highly expressed at the early stages but decreasing trend as fruit reached physiological maturity, which is opposite to the expression profile of MdGH3.18; and a much higher expression level was observed in CP than in GD. Auxin has long been considered a natural inhibitor for fruit ripening as the concentration of auxin is low during pear ripening [57]. It was also observed that as apple ripening began, auxin concentration decreased and ethylene concentration increased [58].…”
Section: The Expression Of Auxin-related Genes and Ethylene Biosynthementioning
confidence: 80%
“…'Bartlett', the changes in the patterns of free auxin and ABA were found to be remarkably similar (Frenkel 1975). Application of relatively higher concentrations of auxin delayed the maturation but at the same time it temporarily stimulates ethylene production (Frenkel and Dyck 1973;Frenkel 1975). These observations were parallel to the results obtained in grape which is a nonclimacteric fruit (Coombe and Hale 1973;Inaba et al 1976;Weaver and Singh 1978;Davies et al 1997;Baydar and Harmankaya 2005).…”
Section: Fruit Ripeningmentioning
confidence: 91%
“…Bartlett) were used as the plant material for this study and were obtained from an orchard located in Amherst, Mass. 3-MeOx was applied to the fruit in a 0.3 M mannitol carrier solution using a vacuum infiltration method (7). The test solutions used consisted of a mannitol control (0 3-MeOx), mannitol control plus ethylene, and 0.1, 1, and 10 Mm of 3-MeOx.…”
Section: Materiails and Methodsmentioning
confidence: 99%